Critical analysis on the choice of Takaful (Islamic insurance) operating models in Malaysia - Htay, Sheila Nu Nu; Zaharin, Hanna Rabittah (2011)
Takaful and insurance have been compared long ago by many scholars around the world. Prior literatures of Takaful are mainly focusing on the concept and theoretical nature of takaful and its differences from insurance. Malaysian Takaful industry has been given flexibility in terms of the operational models adopted and to the researchers’ knowledge; no research has been conducted in Malaysia regarding the choice of Takaful operational models by Takaful operators. It is important to study the motives behind choosing among different Takaful models since different models have different impacts on the surplus distribution of Takaful funds, especially for Family Takaful funds. Therefore, this research is conducted to examine on reasons behind choosing Takaful models and to propose the most suitable model to be adopted by Takaful operators to be fair and equitable for both Takaful operators and participants.